PENDEKATAN STUDI ISLAM DALAM PERSPEKTIF DOSEN DAN MAHASISWA (Studi kasus di UIN Sumatera Utara) - Nurabni; Lathifah Amri Marbun (Universitas Medan Area, 2023)
ABSTRACT, Islamic studies is one of the branch of favorite knowledge to be discussed by experts in knowledge, especially in discussing a method that are used in studyng islam, this case is caused by the weaknesses of the understanding of islam people in learning methodologies, one of the cause is the lack of islam people in understanding methodologies. This thing is go through the development and the MI teachers qualities relate with the understanding of islamic studies it must be with approaches everything that are used in teaching and understanding islamic studies to the students of SD/MI. This writing is purposed to describe two approaches in understanding islamic studies that are methodologies approaches that are needed in understanding islam, also theoric approach is a doctrine that can used to understand islam and how to is the relate between the development and quality increasing of MI teachers.